2019
DOI: 10.1039/c9ta08328f
|View full text |Cite
|
Sign up to set email alerts
|

Achieving high-performance non-halogenated nonfullerene acceptor-based organic solar cells with 13.7% efficiencyviaa synergistic strategy of an indacenodithieno[3,2-b]selenophene core unit and non-halogenated thiophene-based terminal group

Abstract: The combination of indacenodithieno[3,2-b]selenophene core unit and thiophene-containing IC is a successful synergistic strategy with PCE of 13.7%, which is the highest value in NFAs with thiophene-containing IC for binary OSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 90 publications
0
31
0
Order By: Relevance
“…The synthetic routes of TSeIC4Cl and TSeIC4Br were shown in the Scheme and the detailed syntheses were provided in Supporting Information. TSeIC4Cl and TSeIC4Br were synthesized by the Knoevenagel condensation reaction between the central unit TSe‐2CHO [ 86 ] and dichloro‐substituted IC end group ( IC2Cl ) [ 87 ] or dibromo‐substituted IC end group ( IC2Br ) [ 77 ] with isolated yields of 91% and 85%, respectively. Their exact chemical structures are confirmed by 1 H NMR, 13 C NMR, and MALDI‐TOF‐MS, which were shown in support information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic routes of TSeIC4Cl and TSeIC4Br were shown in the Scheme and the detailed syntheses were provided in Supporting Information. TSeIC4Cl and TSeIC4Br were synthesized by the Knoevenagel condensation reaction between the central unit TSe‐2CHO [ 86 ] and dichloro‐substituted IC end group ( IC2Cl ) [ 87 ] or dibromo‐substituted IC end group ( IC2Br ) [ 77 ] with isolated yields of 91% and 85%, respectively. Their exact chemical structures are confirmed by 1 H NMR, 13 C NMR, and MALDI‐TOF‐MS, which were shown in support information.…”
Section: Resultsmentioning
confidence: 99%
“…[ 81–85 ] Recently, our group has synthesized a thiophene‐fused IC‐based NF‐SMA with fused indacenodithieno[3,2‐b]selenophene central core, which presented red‐shift absorption window, higher charge mobility, and higher FF with lower energy loss in comparison with that of NF‐SMAs with indacenodithieno[3,2‐b]thiophene. [ 86 ] Our results indicated that indacenodithieno[3,2‐b]selenophene might be a promising electron‐rich core unit for constructing narrow bandgap tetrabrominated NF‐SMAs. Meanwhile, although bromine has different electronegativity in comparison with that of fluorine and chlorine, very few systematic comparative studies of the effect of replacing difluorinated/dichlorinated IC with dibrominated IC on the terminal group on a pair of tetrahalogenated NF‐SMAs have been thoroughly investigated, especially from the view of obtaining highly efficient tetrabrominated NF‐SMAs.…”
Section: Introductionmentioning
confidence: 90%
“…However, dissymmetric DADc entral core-based NF-SMAs with selenophene seem to be ignored and have seldom been report-ed. [34] This might be due to the great challenges in the chemical synthesis and purification of selenophene-based dissymmetric acceptors.Therefore,toachieve highly efficient (> 17 %) selenophene-based NF-SMAs with high FF and J sc , simultaneously,itis very necessary to implement dissymmetric/symmetric DADc entral cores engineering with selenophene unit and systematically explore the synergistic effect of selenophene and dissymmetric geometry functionalized central core on the electronic property,s ingle crystal packing, film morphology,a nd photovoltaic performance of the NF-SMAs.…”
Section: Introductionmentioning
confidence: 99%
“…Through the modification of donor (D) and/or acceptor (A) fragments, one can control both the band gap and the position of the frontier orbitals to create organic semiconductors with diverse electronic and optical properties. Moreover, organic fluorophores possessing D-A type (some design examples D-A-D, A-D-A, D-π-A, and D-π-A-π-D) structures have been widely used for optoelectronic applications like chemical sensors, biomolecular labels, cellu-lar stains for chemical biology research, organic light-emitting diodes (OLEDs), 1,2 organic solar cells, 3,4 organic transistors 5,6 and charge transfer networks. 7 Three-coordinate triarylborane-based molecules have been attracting a great deal of attention owing to their excellent electronic and photophysical properties for potential applications as fluorescent materials.…”
Section: Introductionmentioning
confidence: 99%